Evaluación de las actividades biológicas in vitro de los aislados proteicos obtenidos a partir de la harina de grillo (Gryllus assimilis). - Quinteros Meneses, María Fernanda (2021)
The insects are currently being investigated as a potential alternative source of protein and nutrients, which makes them important in human nutrition. The high protein content (65 %) allowed the study of its functional properties, gastrointestinal digestibility, antioxidant and anti-inflammatory activity. In this study, protein isolates were obtained from cricket flour (Gryllus assimilis), using different solubilization and precipitation pHs, the protein was quantified by the Dumas, BCA and Bradford method, and analyzed by the SDS-PAGE technique. For the evaluation of the functional properties of the proteins %, solubility %, water and oil absorption capacity were used. In addition, the anti-inflammatory activity and the antioxidant activity were determined by the methods: ABTS, DPPH and FRAP. Cricket protein isolates solubilized at alkaline pHs have high yields (70 %) and protein content of around 80 % in the case of Dumas and over 100 mg of proteins/g sample for colorimetric methods. Cricket meal proteins were characterized by finding protein bands of molecular weights between 250 kDa to 37 kDa. The high percentages of protein solubility, water and oil absorption capacity allowed to establish the use of this by-product as component rich in proteins in various emulsified foods. The protein isolates that presented the highest antioxidant activity were treatments 10.0-4.0, 12.0-6.0 and 10.0-3.0 with values 70.034 mM Trolox / g sample (FRAP), 12.43 mM Trolox / g sample (ABTS) and 68.01 mM Trolox / g sample (DPPH) respectively. The cricket proteins presented up to 93.55 % protection during the inflammation process.